Visible-Light-Activated Graphitic Carbon Nitride/CdS Heterostructure for Superior Photocatalytic Removal of Amoxicillin - Vijayalakshmi, Pandurangan; Sasithra, Visnu (Asian Journal of Chemistry, 2025)
In this study, a S-scheme graphitic carbon nitride/cadmium sulfide (g-C3N4/CdS) nanocomposite was synthesized as well as evaluated of its photocatalytic efficiency within degrading amoxicillin (AMX) from aqueous solutions underneath visible-light exposure. The structural as well optical properties of the nanocomposite were characterized using X-ray diffraction (XRD), UV-Vis diffuse reflectance spectroscopy (UV-DRS), scanning electron microscopy (SEM) and electrochemical impedance spectroscopy (EIS). The g-C3N4/CdS nanocomposite exhibited a narrow band gap of 1.9 eV and achieved an impressive AMX degradation efficiency of 87.08% (rate constant k = 0.0149 min–1) within 150 min, surpassing the performance of the bare nanocomponents. Reactive species trapping experiments identified photogenerated holes (h+) as well as superoxide radicals (O2•-) as the dominant species of active in the degradation processes. Moreover, the photocatalyst demonstrated excellent reusability and chemical stability over three successive cycles, underscoring its potential for practical applications in the removal for organic contaminants in water.